(untitled) (Analele Universității București. Limba și literatură română, 2025)
This paper examines personal narratives of survivors of the wreck of the Empire Patrol, a British ship that was returning 497 inhabitants of Castellorizo, a Greek island in the southeastern Aegean, to their homeland in September 1945, after they had spent two years in a refugee camp in Nuseirat, Gaza. Led by a survivor who was a child at the time of the shipwreck, several survivors memorialized the event by creating a community website, www.empirepatrol.com, in Australia, where their compatriots had already established migrant communities prewar. In this paper, I focus on the survivors’ website-based traumatic narratives and compare them to oral narratives regarding the shipwreck which I recorded while conducting multi-sited, longitudinal and collaborative ethnographic research among the Castellorizians in Australia and in Greece. I explore “orality” in the case of website narratives by examining the new context and symbolism and the performative elements involved, and the community bonds forged among contributors and visitors to the website. I also examine the impact of these digital survivors’ narratives on redefining the sense of belonging and communal identity among Australian-born Castellorizians and on rendering the World War II history of the Castellorizians part of wider public history in Australia.